Perception on the implementation of building information modelling (BIM) in facility management (FM) - Ng, Ching Woon (2023)

(untitled)
BIM is a new popular approach applied in designing and management of a construction building. Its ability to create a virtual model of a physical object and further involve different project stakeholders in the virtual representation to enhance the collaboration and sharing of all critical information before it is being built is in great favour of the construction industry. Its application to FM, however, is still limited. Previous studies had found that the implementation of BIM in FM can bring significant benefits and resulting in lower maintenance and operation costs. Inspired by this, the study is done to determine on the actual factors which drive the intension to use BIM in FM by applying an integrated TAM (Technology Acceptance Model) and TOE (Technology Organization Environment) framework. Factors such as perceived usefulness and perceived ease of use are under the framework of TAM, combined with external factors of technological, organizational, environmental from TOE, meanwhile economic factor is also included to comprehensively determine the relationship between these variables towards the intension of use of BIM in FM. A questionnaire survey was conducted with a total of 102 responses collected. Data analysis was done by using PLS-SEM method. The study's findings found that perceived ease of use is having positive impact towards intension to use BIM in FM, environmental factors are also helping to drive intension to use BIM in FM at the same time. Moreover, it was found that the perceived ease of use of BIM is depending on the technological and organizational factors which have positive significant relation to it. The findings of this study could be a guideline for BIM software developers and policies makers to have an idea on where should the effort be done in order to help in BIM–FM implementation.